Strategies and Barriers in Effective Bus Lane Implementation and Management: Best Practices for Use in the Greater Washington, D.C. Region. Issue 8 (December 2018) - Cesme, Burak; Roisman, Richard; Burns, Ramona; List, Katie; Koudounas, Arrianna; Cuellar, Jesus; Sanders, Meredyth; Lee, Kevin; Miller, David
Bus lanes have the potential to significantly improve bus speeds and reliability. These benefits are typically not solely achieved through the design and installation of a bus lane, however. A successful bus lane must also have sufficient public support for regulating bus lane use, as well as enforcing those regulations. Effective design, enforcement, legislation, and education strategies are critical during both the planning and post-implementation phases to limit bus lane violations and increase compliance, thereby improving bus lane efficiency. Despite the importance of developing a robust management plan to limit violations and maintain bus lane efficiency, there is little documented guidance for bus lane implementation and management in the literature, particularly related to enforcement and education strategies. This paper develops a best practices review to respond to that gap in guidance by conducting a comprehensive literature review of best practice in bus lane management along with interviews with agency staff. The objective of this paper is to research, identify, and develop strategies to improve bus lane observance and enforcement, and to create an implementation plan for agencies with specific recommendations and strategies to ensure the success of bus lane initiatives.